Dimethyl Sulfoxide Decreases Levels of Oxylipin Diols in Mouse Liver - Deol, Poonamjot; Yang, Jun; Morisseau, Christophe; Hammock, Bruce D.; Sladek, Frances M. (Frontiers in Pharmacology, 2019)
Dimethylsulfoxide (DMSO) is widely used as a solvent and cryopreservative in laboratories and considered to have many beneficial health effects in humans. Oxylipins are a class of biologically active metabolites of polyunsaturated fatty acids (PUFAs) that have been linked to a number of diseases. In this study, we investigated the effect of DMSO on oxylipin levels in mouse liver. Liver tissue from male mice (C57Bl6/N) that were either untreated or injected with 1% DMSO at 18 weeks of age was analyzed for oxylipin levels using ultrahigh performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). A decrease in oxylipin diols from linoleic acid (LA, C18:2n6), alpha-linolenic acid (ALA, C18:3n3) and docosahexeanoic acid (DHA, C22:6n3) was observed two hours after injection with DMSO. In contrast, DMSO had no effect on the epoxide precursors or other oxylipins including those derived from arachidonic acid (C20:4n6) or eicosapentaenoic acid (EPA, C20:5n3). It also did not significantly affect the diol:epoxide ratio, suggesting a pathway distinct from, and potentially complementary to, soluble epoxide hydrolase inhibitors (sEHI). Since oxylipins have been associated with a wide array of pathological conditions, from arthritis pain to obesity, our results suggest one potential mechanism underlying the apparent beneficial health effects of DMSO. They also indicate that caution should be used in the interpretation of results using DMSO as a vehicle in animal experiments.